2020
DOI: 10.1177/1060028020964451
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Pirfenidone, Nintedanib, and Pamrevlumab for the Treatment of Idiopathic Pulmonary Fibrosis

Abstract: Background: The comparative efficacy of pirfenidone, nintedanib, and pamrevlumab in slowing the rate of forced vital capacity (FVC) decline and mortality in patients with idiopathic pulmonary fibrosis (IPF) is unknown. Objective: To perform a systematic review and meta-analysis (MA) of these drugs for IPF. Methods: We searched CENTRAL, PubMed, EMBASE, ClincalTrials.gov, and the World Health Organization’s registry databases up to March 2020. Phase II/III randomized controlled trials in adults with IPF were eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…Previous studies have suggested that nintedanib could reduce the decline in forced vital capacity (FVC), preserve quality of life, lower the incidence of acute exacerbations, and increase survival time in patients with IPF [6][7][8]. In previous network meta-analysis of randomized controlled trials (RCTs) comparing 11 treatments in IPF, nintedanib was 1 of 4 medications had benefit, including in pulmonary function decline, exacerbation and mortality [9][10][11][12][13]. More recent studies have shown that nintedanib can also reduce the decline in FVC in patients with systemic sclerosis (SSc)-associated ILD and progressive fibrosis ILD (PF-ILD) in addition to those with IPF [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that nintedanib could reduce the decline in forced vital capacity (FVC), preserve quality of life, lower the incidence of acute exacerbations, and increase survival time in patients with IPF [6][7][8]. In previous network meta-analysis of randomized controlled trials (RCTs) comparing 11 treatments in IPF, nintedanib was 1 of 4 medications had benefit, including in pulmonary function decline, exacerbation and mortality [9][10][11][12][13]. More recent studies have shown that nintedanib can also reduce the decline in FVC in patients with systemic sclerosis (SSc)-associated ILD and progressive fibrosis ILD (PF-ILD) in addition to those with IPF [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The main representative drugs are farnesoid X receptor (FXR) agonists, TGF-β antagonists and Pirfenidone. Among them, nintedanib and pirfenidone, as representative drugs for the treatment of IPF, can slow down the rate of decline of lung function in IPF, and have some effect in reducing the risk of IPF mortality and acute exacerbations, while pamrevlumab has a relatively better effect in reducing the decline of lung function compared with pirfenidone and nintedanib (Di Martino et al, 2021;Petnak et al, 2021). Thus developing more effective antifibrosis drugs or early intervention drugs remains a research hotspot (Ren et al, 2020).…”
Section: New Therapeutic Targets Of Organ Fibrosismentioning
confidence: 99%
“…Studies have shown that it has a good safety profile, and it slows the decline in FVC compared with pirfenidone and nintedanib. It may become a potential IPF treatment [ 67 ]. Further larger trials are needed.…”
Section: Reviewmentioning
confidence: 99%